2020 Security Review: A Year That Shook IT. (24th December 2020) - O'Connor, Patrick
Abstract: Reviewing IT security incidents in 2020, Patrick O'Connor MBCS CISSP CEH, finds that while society may have slowed to a crawl in the face of Covid-19 the cyber security world is more active than ever.